Interplay of Phonon Directionality and Emission Polarization in Two-Dimensional Layered Metal Halide Perovskites - Krahne, Roman; Lin, Miao-Ling; Tan, Ping-Heng (Accounts of chemical research, 2024)
Conspectus Layered metal halide perovskites represent a natural quantum well system for charge carriers that provides rich physics, and the organic encapsulation of the inorganic metal halide layers not only increases their stability in devices but also provides an immense freedom to design their functionality. Intriguingly, these organic moieties strongly impact the optical, electrical, and mechanical properties, not only through their dielectric, elastic, and chemical properties but also because of induced mechanical distortions in the inorganic lattice. This tunability makes two-dimensional layered perovskites (2DLPs) highly attractive as light emitters. Common consensus is that exciton–phonon coupling plays an important role in radiative recombination. For bulk and some two-dimensional (2D) materials, the band edge emission broadening can be described by the classic models for polar inorganic semiconductors, while for the temperature dependence of the self-trapped exciton emission, an analysis developed for color centers has been successfully applied. For many 2DLPs these approaches do not work because of the complexity of their vibrational spectra. However, their emission is still strongly determined by phonons, and therefore, an adequate understanding of the electron–phonon coupling needs to be developed. With polarized and angle-resolved Raman spectroscopy studies on single 2DLP flakes based on different ammonium molecules as organic cations, in 2020 we revealed very rich phonon spectra in the low-frequency regime. Although the phonon bands at low frequency can generally be attributed to the vibrations of the inorganic lattice, we found very different responses by only changing the type of organic cations. In addition, the intensity of the different phonon modes depended strongly on the angle of the linearly polarized excitation beam with respect to the in-plane axes of the octahedron lattice. In 2022, we mapped this angular dependence of the phonon modes, which allowed identification of the directionality of the different lattice vibrations. By correlating the phonon spectra with the temperature-dependent emission for a set of 2DLPs that featured very different self-trapped exciton (STE) emission, we demonstrated that the exciton relaxation cannot be related to coupling with a single (longitudinal-optical) phonon band and that several phonon bands should be involved in the emission process. To gain insights into the exciton–phonon coupling effects on the band edge emission, we performed both angle-resolved polarized emission and Raman spectroscopy on single 2D lead iodide perovskite microcrystals. These experiments revealed the impact of the organic cations on the linear polarization of the emission and corroborated that multiple phonon bands should be involved in the radiative recombination process. Analysis of the temperature-dependent line width broadening of the band edge emission showed that for many systems, the behavior cannot be described by assuming the involvement of only one phonon mode in the electron–phonon coupling process. Our studies revealed a wealth of highly directional low-frequency phonons in 2DLPs from which several bands are involved in the emission process, which leads to diverse optical and vibrational properties depending on the type of organic cation in the material.